Role of endoplasmic reticulum autophagy in acute lung injury - Liu, Shiping; Fang, Xiaoyu; Zhu, Ruiyao; Zhang, Jing; Wang, Huijuan; Lei, Jiaxi; Wang, Chaoqun; Wang, Lu; Zhan, Liying (Frontiers in Immunology, 2023)
Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS), the prime causes of morbidity and mortality in critically ill patients, are usually treated by general supportive treatments. Endoplasmic reticulum autophagy (ER-phagy) maintains cellular homeostasis by degrading damaged endoplasmic reticulum (ER) fragments and misfolded proteins. ER-phagy is crucial for maintaining ER homeostasis and improving the internal environment. ER-phagy has a particular role in some aspects, such as immunity, inflammation, cell death, pathogen infection, and collagen quality. In this review, we summarized the definition, epidemiology, and pathophysiology of ALI/ARDS and described the regulatory mechanisms and functions of ER-phagy as well as discussed the potential role of ER-phagy in ALI/ARDS from the perspectives of immunity, inflammation, apoptosis, pathogen infection, and fibrosis to provide a novel and effective target for improving the prognosis of ALI/ARDS.